Causative eventive chains and selection of affixes in Portuguese nominalisations - Rodrigues, Alexandra Soares (2015)
In Portuguese, different suffixes are used to construct event deverbal nouns from the same base verb. In this paper, we focus on deverbal nouns constructed from causative verbs. Being event nouns, the meanings of the derivatives of these suffixes differ slightly. We aim to contribute to the understanding of the mechanisms involved in semantic rivalry between affixes, specifically with regard to the knowledge of the semantic features of the verbal base that are sensitive to the semantics of each affix. We propose that the semantic features of the affix must be semantically compatible with semantic features of the lexical-semantic structure of the base verb. Because of a coindexation mechanism (Lieber 2004), the semantic features of the affix will coindex with the semantic features of the verb that are most compatible with its own features (Rodrigues & Rio-Torto 2013; Rodrigues 2008). Our hypothesis permits us to explain why there are so many verbs with different deverbal nouns, with different affixes. The affixes in those situations are not acting as rivals, since they are not competing with each other to exclude each other.